In-house Aligners: Why We Should Fabricate Aligners in Our Clinics? - Murat Tozlu; Fulya Ozdemir (Galenos Yayinevi, 2021)
As digital dentistry is evolving, contemporary orthodontics is embracing clear aligners as a tool more than ever before. On the other hand, aligners are being marketed to patients by aligner companies in every way that is possible. The demand of the end user and the pursuit of the orthodontist toward less chair time has made aligners popular in the last decade. As the price for having all machinery needed to fabricate aligners has decreased, orthodontists may choose to fabricate aligners in-house. In-house fabrication will bring advantages in the price, delivery time, and doctor's time if it is done correctly.